Analisis Penurunan Tekanan Hp Drum HRSGDI PLTGU Grati Setelah Exhaust Damper Close - Roswati Nurhasanah; Puri Hariadi (Sekolah Tinggi Teknik - PLN, 2015)
Long or short time in PLTGU GRATI HSRG operate depending on the conditions of pressure HP Drum. These pressures affect the waiting time ranges for each stage of the opening of the exhaust damper. If during the stand-by pressure HP Drum quickly run up to the pressure of <5 kg / cm2 then to operate it back it took a long time because the status has changed into a Cold. In order for the operation of the HRSG does not require a long time start-up should be done when the pressure is> 15 kg / cm2 more precisely the conditions Hot. Based on the observation chart ONLINE TEMP known cause of the pressure drop HP Drum very drastic happens during the process of the HRSG is shut down simultaneously with the circulation of HP BCP for 30 minutes after closing Exhaust Damper. From the calculation of the amount of energy lost (q loss) amounted to 1122.6 kW disistem and almost proportional to the amount of energy out of the system through the HP economizer amounted to 1328.2 kW net of energy absorption (q save) from HP Evaporator.